Ceramic Armor as Protective Material in Defense Industry Product: A Literature Review - Ary Lestari; Leni Tria Melati; Kasim Kasim; Jupriyanto Jupriyanto; George Royke Deksino (Indonesian Mechanical Electrical and Industrial Research Society (IMEIRS), 2023)
Ceramics are currently widely used in various defense industries. Among them are the purposes of body armor (vests and helmets), vehicle protection, and ballistic protection. This review aims to provide insight into ceramic armor materials including their manufacture, use, and application as protective materials. The method used is a literature review and describes the results of the analysis related to the application of ceramic materials in the form of ceramic armor. The use of ceramic armor materials in defense industry products is proven to provide good performance compared to metal materials, especially in increasing the mobility capabilities of defense personnel. In addition, the use of ceramic armor has initiated the development of lightweight protective materials so that various technologies have been developed to maximize the use of ceramics in the defense industry. Keramik saat ini banyak digunakan dalam berbagai industri pertahanan. Diantaranya untuk keperluan bahan pelindung tubuh (rompi dan helm), pelindung kendaraan, dan pelindung balistik. Review ini bertujuan untuk memberikan wawasan tentang material armor keramik yang meliputi pembuatan, penggunaan, dan aplikasinya sebagai bahan pelindung. Metode yang digunakan adalah literatur review dan mendeskripsikan hasil analisa terkait aplikasi material keramik dalam bentuk ceramic armor. Pemanfaatan material armor keramik pada produk industri pertahanan terbukti dapat memberikan performa yang baik dibandingkan dengan material logam terutama dalam meningkatkan kemampuan mobilitas dari personil pertahanan. Selain itu penggunaan armor keramik telah menginisiasi pengembangan material pelindung ringan sehingga berbagai macam teknologi dikembangkan untuk dapat memaksimalkan penggunaan keramik dalam industri pertahanan.